Intra‐arterial renal infusion of autologous mesenchymal stem cells for treatment of chronic kidney disease in cats: Phase I clinical trial. (29th March 2019) - Thomson, Abigail L.; Berent, Allyson C.; Weisse, Chick; Langston, Catherine E.
Abstract: Background: There are no known treatments that halt or reverse chronic kidney disease (CKD) in cats. In rodent models, stem cell treatment has been associated with improvement in renal function parameters, especially when stem cells were delivered intra‐arterially to the kidney. To date, only IV and intrarenal stem cell infusions have been studied in cats with CKD with no clinically relevant improvement noted. Objective: To assess the safety and feasibility of intra‐arterial delivery of autologous mesenchymal stem cells (MSC) in stromal vascular fraction (SVF) to the kidney in cats with CKD. Animals: Five client‐owned domestic cats with International Renal Interest Society stage III CKD. Methods: Prospective cohort study (phase I clinical trial). Adipose tissue was harvested from study animals on day 0. On days 2 and 14, an infusion of MSC in SVF was administered into the renal artery via the femoral or carotid artery using fluoroscopic guidance. Serum creatinine and blood urea nitrogen concentration, plasma iohexol clearance, and quality of life assessments were monitored between days 0 and 90. Results: The procedure was performed successfully in all cats. No severe adverse events were observed in any cat during the study period. Conclusions and Clinical Importance: Intra‐arterial infusion of MSC into the renal artery in CKD cats was feasible and safe within a 3‐month postoperative period. Efficacy and long‐term safety have yet to be established. This procedure requires careful technique and training.